A canonical basis approach to unitarity calculations in Yang-Mills theories. - Edmund Warrick (2011)
A Canonical Basis m ethod is presented for computing the cut-constructible parts of loop amplitudes in massless Yang-Mills theory by generalised Unitarity. The method relies upon constructing a canonical basis of general cut solutions and constructing the amplitude by identifying the integral coefficients with elements of the canonical basis, thereby avoiding repeated integration of similar integrand structures. The method provides closed, rational, fully analytic expressions for the integral coefficients. As an application the m ethod is applied to compute the previously unknown NMHV partial amplitudes of the 7-gluon Af = 1 chiral multiplet loop, and is then extended to rederive the cut-constructible terms of the NMHV 6-gluon partial amplitudes with a complex scalar loop.